2012
DOI: 10.2337/db11-1516
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Insulin Exocytosis in Human Pancreatic β-Cells With Gene Variants Linked to Type 2 Diabetes

Abstract: The majority of genetic risk variants for type 2 diabetes (T2D) affect insulin secretion, but the mechanisms through which they influence pancreatic islet function remain largely unknown. We functionally characterized human islets to determine secretory, biophysical, and ultrastructural features in relation to genetic risk profiles in diabetic and nondiabetic donors. Islets from donors with T2D exhibited impaired insulin secretion, which was more pronounced in lean than obese diabetic donors. We assessed the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
189
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 212 publications
(218 citation statements)
references
References 41 publications
18
189
0
2
Order By: Relevance
“…In the publication by Xia et al, a similar picture could be seen in the chromatin capture data, which demonstrated a direct physical interaction between the rs7903146-containing enhancer and the TCF7L2 promoter [6]. There is a clear relationship between the type 2 diabetes-associated variants at TCF7L2 and altered islet function, which has been observed both in physiological data from non-diabetic individuals [3], as well as in glucose-stimulated insulin secretion measures in human islet culture [11]. Modulation of TCF7L2 expression in human islets affects their function, but since Xia and colleagues have performed their experiments in human colon cell lines and tissue [6], it is not known whether ACSL5 remains a target of type 2 diabetes variants in islets.…”
supporting
confidence: 55%
“…In the publication by Xia et al, a similar picture could be seen in the chromatin capture data, which demonstrated a direct physical interaction between the rs7903146-containing enhancer and the TCF7L2 promoter [6]. There is a clear relationship between the type 2 diabetes-associated variants at TCF7L2 and altered islet function, which has been observed both in physiological data from non-diabetic individuals [3], as well as in glucose-stimulated insulin secretion measures in human islet culture [11]. Modulation of TCF7L2 expression in human islets affects their function, but since Xia and colleagues have performed their experiments in human colon cell lines and tissue [6], it is not known whether ACSL5 remains a target of type 2 diabetes variants in islets.…”
supporting
confidence: 55%
“…Moreover, non-obese individuals with heredity for type 2 diabetes display WAT hypertrophy and insulin resistance [12]. Although type 2 diabetes in lean individuals is most often linked to beta cell dysfunction [13], an important contributing factor could be impaired expansion of WAT resulting in ectopic fat accumulation. This notion is convincingly illustrated by lipodystrophies caused by disturbed function of genes that regulate adipogenesis or lipid storage (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes-associated TCF7L2 SNPs have been associated with impaired pancreatic beta cell function, e.g. reduced insulin exocytosis [2], and a reduction in glucagon-like peptide-1-induced insulin secretion [3][4][5]. Human carriers of the TCF7L2 rs7903146 risk allele have increased pancreatic islet size, and altered alpha:beta cell ratios and distribution within pancreatic islets [6].…”
Section: Introductionmentioning
confidence: 99%